In Pursuit of Adult Progenitors of Thymic Epithelial Cells - Ishikawa, Tatsuya; Akiyama, Nobuko; Akiyama, Taishin (Frontiers in Immunology, 2021)
Peripheral T cells capable of discriminating between self and non-self antigens are major components of a robust adaptive immune system. The development of self-tolerant T cells is orchestrated by thymic epithelial cells (TECs), which are localized in the thymic cortex (cortical TECs, cTECs) and medulla (medullary TECs, mTECs). cTECs and mTECs are essential for differentiation, proliferation, and positive and negative selection of thymocytes. Recent advances in single-cell RNA-sequencing technology have revealed a previously unknown degree of TEC heterogeneity, but we still lack a clear picture of the identity of TEC progenitors in the adult thymus. In this review, we describe both earlier and recent findings that shed light on features of these elusive adult progenitors in the context of tissue homeostasis, as well as recovery from stress-induced thymic atrophy.